PEMBAGIAN WARISAN MASYARAKAT BATAK TOBA (Studi Kasus Masyarakat Batak Toba Di Kota Pekanbaru) - Buana Nadapdap; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at Labuh Baru Barat Village, Payung Sekaki District, Pekanbaru City, Riau Province. The purpose of this research is to describe the distribution system of the Toba Batak Customary inheritance and its shift and to find out the social conditions underlying the shift in the inheritance distribution system for the Toba Batak Indigenous. As for the subjects of the study were the Toba Batak Tribe in Pekanbaru City. The data analysis technique is done qualitatively by using descriptive data analysis of the data obtained in the field in the form of words. The conclusions that can be drawn from this study are 1) The implementation of inheritance distribution according to traditional Toba Batak is given to boys while women only receive daily care (sileon-leon / voluntary assistance provided by their parents or brothers). The distribution of inheritance is given more to boys because the family tree is based on boys, the responsibilities of men are greater to the family, and those who represent their parents in customary activities, and also to achieve the goals or philosophy of the hobo people which is the basis of the life of the Batak people. 2) The division of Toba Batak inheritance in Pekanbaru City has undergone a shift. In the distribution of the inheritance of the Toba Batak community in the area, that is still following the custom that has been adopted for a long time, which states that the inheritance of the parents falls to boys while the women cannot. However, for the Toba Batak community in Pekanbaru City, especially for those who have long migrated their inheritance, they do not follow the Toba Batak custom anymore because they give their children inheritance based on their own desires depending on the needs of each child, because according to most Batak Toba in Pekanbaru City, the distribution of inheritance according to the custom of the Toba Batak from their ancestors was unfair because it only concerned the needs of boys. Keywords: Inheritance and Batak Toba